The narrations contained in the book “The Meanings of the Qur’an” by Imam Al-Farra’ (d. 207 AH) from the beginning of the book to Surat Al-Isra’, collection and study (Islamic Sciences Journal, 2024)
ABSTRACTThis book explains the most important books of hadith, which are the narrations attributed in the book Meanings of the Qur’an. This topic has not been written in a scientific treatise, according to my knowledge. My love for the science of hadith, which is one of the most honorable sciences, and my desire for it to be the subject of my research in it, and to be informed of the words of scholars in it, so I found this. The topic fulfills my scientific desire, the approval and encouragement that I received from the distinguished professors who have great experience in this specialty, which increased my activity - after relying on Allah Almighty - in researching this topic.
Keywords: The novel, the meanings of the Qur’an, Al-Farra’, the Hadith.